2021
DOI: 10.1021/acscatal.1c02315
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Types and Origin of Active Oxygen Species Present in Supported Mn-Na2WO4/SiO2 Catalysts for Oxidative Coupling of Methane

Abstract: The involvement of lattice oxygen species is important toward oxidative coupling of the methane reaction (OCM) over supported Mn-Na 2 WO 4 /SiO 2 catalysts, but there is no consensus regarding the types, role, and origin of lattice oxygen species present in supported Mn-Na 2 WO 4 /SiO 2 catalysts, which hinders the understanding of the OCM reaction network. In the present study, by utilizing the temporal analysis of products technique, we show that supported Na 2 WO 4 /SiO 2 catalysts possess two different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 18 publications
1
54
2
Order By: Relevance
“…Because such multiple synergy is expected to occur only slightly when using a conventional method, this new finding is anticipated as a predominant protocol for ML-aided catalyst investigation. Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because such multiple synergy is expected to occur only slightly when using a conventional method, this new finding is anticipated as a predominant protocol for ML-aided catalyst investigation. Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the role of Mn still remains an open question in OCM studies. ,, For instance, there has been reports on not only the positive effect in Mn-Na 2 WO 4 /SiO 2 and K x MnO y /SiO 2 but also the negative effect in the La 2 O 3 - or MgO-based catalyst . Because under the OCM the following occur: (i) C 2 production is influenced not only via the surface of catalyst but also via the outer surfaces (gas-phase) reaction. (ii) The reaction usually performs under a high reaction temperature above melting points of metal components. (iii) Synergy of components might be different from kinds of support, ,, and the effect of Mn in OCM under operation conditions is still a controversial subject. In other words, it is demonstrated that the HTS data-driven ML approach can aid catalyst investigation without scientists’ experiences and discover the positive fourth element (viz.…”
Section: Resultsmentioning
confidence: 99%
“… 64 A recent temporal analysis of products (TAP) reactor study of crystalline phase Mn–Na 2 WO 4 /SiO 2 catalysts further elucidated that the Na 2 WO 4 /SiO 2 catalyst (without Mn-oxide) possesses two distinct kinds of oxygen species at 800 °C: (i) a dissolved molecular O 2 type species only released from the molten Na 2 WO 4 phase and (ii) an atomic lattice O type species associated with surface Na–WO 4 sites that can be removed by reduction with CH 4 . 65 Both these oxygen species are catalytically active for the OCM reaction. On the other hand, the 1.2Mn/SiO 2 catalyst (without Na 2 WO 4 ) only provides molecular O 2 type species associated with the Mn-oxide phase, and no atomic O type species.…”
Section: Resultsmentioning
confidence: 99%
“…The O 2 species associated with the Mn-oxide phase were found to highly unselective toward C 2 product formation from CH 4 activation. 65 It would be interesting to conduct a similar TAP reactor study on model catalysts in the absence of crystalline oxide phases with only dispersed surface sites present to compare how such dispersed sites function versus the respective crystalline oxide phase.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed kinetic and mechanistic characterization is needed to better understand how different catalyst components contribute to both C 2 and CO 2 formation pathways. Our previous findings, using TAP titration and pump/probe methods together with operando Raman characterization, indicate that the addition of Mn oxide to the supported Na 2 WO 4 /SiO 2 catalyst increases the total amount and release rate of oxygen species . In this study, we systematically investigated how each catalyst component and its combinations impact OCM performance and selective/nonselective mechanistic pathways through transient kinetic characterization.…”
Section: Introductionmentioning
confidence: 99%